2021
DOI: 10.1371/journal.pone.0261358
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine use in patients with COVID-19: A systematic review and meta-analysis

Abstract: Introduction Colchicine may inhibit inflammasome signaling and reduce proinflammatory cytokines, a purported mechanism of COVID-19 pneumonia. The aim of this systematic review and meta-analysis is to report on the state of the current literature on the use of colchicine in COVID-19 and to investigate the reported clinical outcomes in COVID-19 patients by colchicine usage. Methods The literature was searched from January 2019 through January 28, 2021. References were screened to identify studies that reported… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
20
1
1
Order By: Relevance
“…Although earlier meta-analysis performed by Chiu et al, 18 Vrachatis et al, 19 Hariyanto et al, 20 Salah et al, 21 Elshafei et al, 22 Golpour et al, 23 and Beran et al 24 concluded that colchicine may reduce the risk of mortality in patients with COVID-19 infection, we found no mortality benefit when adding colchicine to the usual care of hospitalized patients with this type of viral infection. The discrepancy with our results and with the recent meta-analysis performed by Kow et al 25 and Mehta et al 26 could be partially explained by the inclusion of only randomized clinical trials instead of a mixture of observational plus randomized studies.…”
contrasting
confidence: 66%
“…Although earlier meta-analysis performed by Chiu et al, 18 Vrachatis et al, 19 Hariyanto et al, 20 Salah et al, 21 Elshafei et al, 22 Golpour et al, 23 and Beran et al 24 concluded that colchicine may reduce the risk of mortality in patients with COVID-19 infection, we found no mortality benefit when adding colchicine to the usual care of hospitalized patients with this type of viral infection. The discrepancy with our results and with the recent meta-analysis performed by Kow et al 25 and Mehta et al 26 could be partially explained by the inclusion of only randomized clinical trials instead of a mixture of observational plus randomized studies.…”
contrasting
confidence: 66%
“…With regard to the data from systematic reviews and meta-analyses, including randomized clinical trials and observational studies, regarding the use of colchicine in COVID-19, controversial results have been reported, mostly due to the number and type of articles included at different times during the COVID-19 pandemic. While several meta-analyses of randomized clinical trials [ 52 55 ] and observational studies [ 56 , 57 ] have provided negative or inconclusive results regarding the role of colchicine in COVID-19 mortality, a higher number of these studies found positive effects of colchicine in terms of reduction of hospital admissions [ 52 ], hospitalization time [ 58 ], and mortality [ 53 , 54 , 59 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral activity of this alkaloid is attributed to its ability to bind tubulin dimers and inhibit microtubule assembly, which not only promotes anti-inflammatory effects but also makes colchicine a potent mitotic poison [ 154 , 157 ]. In addition, colchicine may inhibit inflammasome signaling and reduce proinflammatory cytokines, which is a purported mechanism of COVID-19 pneumonia [ 158 ].…”
Section: Alkaloidsmentioning
confidence: 99%